Evidence for the continued use of river dolphin oil for bait fishing and traditional medicine: implications for conservation - Vishnupriya Kolipakam; Shweta Singh; Shovana Ray; Leela Prasad; Kanad Roy; Abdul Wakid; Qamar Qureshi (Heliyon, 2020)
Populations of the Ganges river dolphin (Platanista gangetica gangetica) are endangered, with ~3500 individuals estimated worldwide. Threats to this precarious population is exacerbated by accidental entanglement and illegal hunting for oil, which is used in bait fisheries and traditional medicine. Alternatives to dolphin oil have been proposed and extensively promoted in India, to curb the immediate threat to dolphin populations. However, it is not known whether dolphins are still being poached for oil, despite the proposal of aforementioned alternatives. Herein, a molecular protocol to monitor the presence of Dolphin DNA, using species identification of DNA extracted from bait oils obtained from fishermen is presented. This is coupled with information from social surveys to understand the current status of use of dolphin oil. Results indicate that molecular tools provide an accurate technique for detecting the presence of dolphin DNA, and can be used by enforcement agencies to monitor and identify points of threat to dolphins. Social survey results indicate the preference of fishermen to continue the use of dolphin oil for bait, despite knowing the legal implications. It is found that alternate oils do not provide an effective solution to curb dolphin oil use, and only shifts the threats of endangerment from one species to another, in the long run. The ban of bait fishing, effective enforcement combined with monitoring through molecular tools, continued community engagement and livelihood skill development are the most viable solutions for a holistic conservation approach.